Stated Preference Analysis of Feeder Service Plan from STTD to Jatimulya LRT Station, East Bekasi - Dwi Prasetyo Sayoto Putro; Tiara Ayustian; Angelina Wahyu Christyani; Yugihartiman ATD (Jurnal Siber Multi Disiplin, 2026)
Development feeder services have role important in increase first-mile and last-mile integration towards system transport mass rail- based research This aim For analyze preference users to plan feeder service from STTD to Jatimulya LRT Station , East Bekasi uses Stated Preference approach and Nested Logit model. Research data obtained through survey of 276 respondents consisting​ on students, STTD staff, and the community around STTD and Grand Wisata areas . Analyzed attributes covering time travel, costs travel, frequency service , rates, and comfort . Research results show that frequency service, time travel, and fares is factor main influencing factors election mode . Feeder services have probability more elections​ tall compared to a number of fashion others , especially in conditions frequency high service and affordable rates. The model estimation results show that attribute time travel, costs travel, and fares influential negative to utilities mode, whereas frequency service influential positive to probability feeder selection . Willingness to Pay (WTP) analysis shows that respondents willing pay more For get service with time wait for more short and certain more schedule​ good. Findings study This show that development integrated feeder services with LRT potential push displacement use vehicle personal going to transportation more general​ sustainable